Diseño de manual de uso y reúso de fresas de uso odontológico en la clínica de la universidad Antonio Nariño sede Cúcuta (2025)
Dentists in training, despite having a use and reuse manual, present shortcomings in the application of the protocol, generating failures in the disinfection and reuse of dental burs